Thoracic lymphatic anomalies in patients with univentricular hearts: correlation of morphologic findings in isotropic T2-weighted MRI with the outcome after fontan palliation - Hanser, Anja; Hofbeck, Michael; Hofmeister, Melanie; Martirosian, Petros; Hornung, Andreas; Esser, Michael; Schick, Fritz; Kaulitz, Renate; Michel, Jörg; Nikolaou, Konstantin; Schäfer, Jürgen; Schlensak, Christian; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objectives In this study we examined the correlation between the extent of thoracic lymphatic anomalies in patients after surgical palliation by total cavopulmonary connection (TCPC) and their outcome in terms of clinical and laboratory parameters. Materials and methods We prospectively examined 33 patients after TCPC with an isotropic heavily T2-weighted MRI sequence on a 3.0 T scanner. Examinations were performed after a solid meal, slice thickness of 0.6 mm, TR of 2400 ms, TE of 692 ms, FoV of 460 mm, covering thoracic and abdominal regions. Findings of the lymphatic system were correlated with clinical and laboratory parameters obtained at the annual routine check-up. Results Eight patients (group 1) showed type 4 lymphatic abnormalities. Twentyfive patients (group 2) presented less severe anomalies (type 1–3). In the treadmill CPET, group 2 reached step 7.0;6.0/8.0 vs. 6.0;3.5/6.8 in group 1 (p = 0.006*) and a distance of 775;638/854 m vs. 513;315/661 m (p = 0.006*). In the laboratory examinations, group 2 showed significantly lower levels of AST, ALT and stool calprotectin as compared to group 1. There were no significant differences in NT-pro-BNP, total protein, IgG, lymphocytes or platelets, but trends. A history of ascites showed 5/8 patients in group 1 vs. 4/25 patients in group 2 (p = 0.02*), PLE occurred in 4/8 patient in group 1 vs. 1/25 patients in group 2 (p = 0.008*). Conclusion In the long-term follow-up after TCPC, patients with severe thoracic and cervical lymphatic abnormalities showed restrictions in exercise capacity, higher liver enzymes and an increased rate of symptoms of imminent Fontan-failure such as ascites and PLE.